Sufistic Urgency In Influencing The Psychology Of Self-Control Of One's Behavior - Ahmad Muhammad Al Karofi (Da'wa Faculty of Islamic State University Salatiga, 2023)
In the learning concept of Islamic religious education more specifically like Sufism is more directed towards multicultural experience, so that Sufism leaders in developing their teachings towards the development of good morals, by going through two things, the first is how to be adab in facing Allah, and the second is in behave well to fellow human beings. This research is included in the descriptive type of qualitative analysis by collecting and tracing existing data literature, this method includes without the need to go directly into the field and only limit it to related data. This study aims to determine the impact of mysticism which influences psychology on a person's behavior which makes a better person. The results of the study show that psychology in a sufistic approach is able to direct individual mindsets in behavior so that they are able to control themselves in a better direction, by going through the stages that must be passed so as to get maximum results.